Adrenergic regulation of innate immunity: a review - Scanzano, Angela; Cosentino, Marco (Frontiers in Pharmacology, 2015)
The sympathetic nervous system has a major role in the brain-immune cross-talk, but few information exist on the sympathoadrenergic regulation of innate immune system.The aim of this review is to summarize available knowledge regarding the sympathetic modulation of the innate immune response, providing a rational background for the possible repurposing of adrenergic drugs as immunomodulating agents. The cells of immune system express adrenoceptors (AR), which represent the target for noradrenaline and adrenaline. In human neutrophils, adrenaline and noradrenaline inhibit migration, CD11b/CD18 expression, and oxidative metabolism, possibly through β-AR, although the role of α1- and α2-AR requires further investigation. Natural Killer express β-AR, which are usually inhibitory. Monocytes express β-AR and their activation is usually antiinflammatory. On murine Dentritic cells (DC), β-AR mediate sympathetic influence on DC-T cells interactions. In human DC β2-AR may affect Th1/2 differentiation of CD4+ T cells. In microglia and in astrocytes, β2-AR dysregulation may contribute to neuroinflammation in autoimmune and neurodegenerative disease. In conclusion, extensive evidence supports a critical role for adrenergic mechanisms in the regulation of innate immunity, in peripheral tissues as well as in the CNS. Sympathoadrenergic pathways in the innate immune system may represent novel antiinflammatory and immunomodulating targets with significant therapeutic potential.